BMP6 binding to heparin and heparan sulfate is mediated by N-terminal and C-terminal clustered basic residues - Denardo, Andrea; Elli, Stefano; Federici, Stefania; Asperti, Michela; Gryzik, Magdalena; Ruzzenenti, Paola; Carmona, Fernando; Bergese, Paolo; Naggi, Annamaria; Arosio, Paolo; Poli, Maura (Biochimica et biophysica acta. General subjects, 2021)
The bone morphogenetic protein 6 (BMP6) is a crucial inducer of hepcidin, the peptide hormone that regulates the iron availability in our body. Hepcidin expression is influenced by hepatic heparan sulfate (HS) and by heparin administration, suggesting BMP6 interaction with heparin/HS. The BMP2/4 subfamily has been deeply characterized to have a N-terminal heparin/HS binding domain (HBD), whose basic residues contact the sulfate groups on heparin and HS. Such detailed characterization is still required for other, structurally different BMPs, including BMP6. BMP6 peptides encompassing potential HBDs were analysed on heparin-functionalized plates and microcantilevers, and on membrane HS expressing CHO-K1 cells. Monomeric wild-type BMP6 and mutants were produced, substituting the basic residues with non-charged ones, and their affinity to the heparin-column was measured. The BMP6-heparin interaction was also predicted at atomic level by in silico molecular dynamics. N-terminal and C-terminal BMP6 peptides showed high heparin affinity in solid-phase assays. The mutation of the two sites (R5L, R6S, R7L and K126N, K127N, R129S) abolished the heparin-binding activity of the recombinant monomeric BMP6. Monomeric BMP6 and peptides specifically bound to membrane HS of CHO-K1 cells through the same domains. Molecular dynamic studies supported the role of the two HBDs, suggesting a cooperative behaviour. In BMP6, N-terminal (R5, R6, R7) and C-terminal (K126, K127, R129) domains mediate the interaction with heparin and HS. This study provides the molecular mechanism supporting the use of heparin to sequester BMP6 and inhibit hepcidin expression, a novel clinical approach for high-hepcidin iron disorders. •Arginine- and Lysine-rich regions were identified on BMP6 as potential heparin/HS-binding domains (HBDs).•BMP6 peptides and recombinant protein bound immobilized heparin and HS.•We dissected two heparin binding sites on BMP6: the N-terminal R5 R6 R7 and the C-terminal K126 K127 R129.•In in silico study the N-terminus flexibly adapted to heparin and the C-terminus strongly contributed to binding energy.